Environmental, social, and governance performance, financing constraints, and corporate investment efficiency: Empirical evidence from China - Wei Li; Jian Zhu; Changqing Liu (Heliyon)
This study explores the connection between environmental, social, and governance (ESG) performance, financing constraints, and corporate investment efficiency. The hypotheses in this study are formulated based on the principles of stakeholder and agency theories. We used secondary data from Chinese A-share listed companies from 2010 to 2021 to conduct an empirical analysis using the Ordinary Least Squares (OLS) and Fixed Effect (FE) estimators. The results indicate that good ESG performance can enhance corporate investment efficiency. Compared to over-investment, ESG performance has a more pronounced effect on mitigating under-investment. Using a mediating analysis model, we also find that ESG performance exerts an inhibitory influence on both under- and over-investments by mitigating corporate financing constraints. Heterogeneity analysis indicates that the enhancing effect of ESG performance on corporate investment efficiency is more significant in non-state-owned corporations, low-pollution corporations, and corporations with a higher proportion of institutional investors. This study provides insights for listed companies to improve ESG performance to enhance capital allocation efficiency and promote sustainable development.